Correlation between cytotoxicity and DNA binding of polypyridyl ruthenium complexes - Nováková, O; Kaspárková, J; Vrána, O; van Vliet, P M; Reedijk, J; Brabec, V (Biochemistry, 1995)
The cytotoxicity of chloropolypyridyl ruthenium complexes of structural formulas [Ru(terpy)-(bpy)Cl]Cl, cis-[Ru(bpy)2Cl2], and mer-[Ru(terpy)Cl3] (terpy = 2,2':6'2"-terpyridine, bpy = 2,2'-bipyridyl) has been studied in murine and human tumor cell lines. The results show that mer-[Ru(terpy)Cl3] exhibits a remarkably higher cytotoxicity than the other complexes. Moreover, investigations of antitumor activity in a standard tumor screen have revealed the highest efficiency for mer-[Ru(terpy)Cl3]. In a cell-free medium, the ruthenium complexes coordinate to DNA preferentially at guanine residues. The resulting adducts can terminate DNA synthesis by thermostable VentR DNA polymerase. The reactivity of the complexes to DNA, their efficiency to unwind closed, negatively supercoiled DNA, and a sequence preference of their DNA adducts (studied by means of replication mapping) do not show a correlation with biological activity. On the other hand, the cytotoxic mer-[Ru(terpy)Cl3] exhibits a significant DNA interstrand cross-linking, in contrast to the inactive complexes which exhibit no such efficacy. The results point to a potential new class of metal-based antitumor compounds acting by a mechanism involving DNA interstrand cross-linking.
Keywords: Cross-Linking Reagents; DNA-dependentní DNA-polymerasy; 2,2'-Dipyridyl; Toxicity Tests; testy toxicity; Humans; HeLa buňky; sekvence nukleotidů; Molecular Sequence Data; 2,2'-dipyridyl; molekulární sekvence - údaje; Dose-Response Relationship, Drug; Antineoplastic Agents; DNA-Directed DNA Polymerase; lidé; Organometallic Compounds; zvířata; reagencia zkříženě vázaná; myši; Mice; organokovové sloučeniny; DNA Replication; superhelikální DNA; Base Sequence; Leukemia L1210; HeLa Cells; replikace DNA; konformace nukleové kyseliny; protinádorové látky; Nucleic Acid Conformation; vztah mezi dávkou a účinkem léčiva; Animals; leukemie L1210; DNA, Superhelical; adukty DNA; DNA Adducts